Casting a look at pediatric plastic bronchitis. Issue 10 (October 2015) - Jasinovic, Tin; Kozak, Frederick K.; Moxham, J. Paul; Chilvers, Mark; Wensley, David; Seear, Michael; Campbell, Andrew; Ludemann, Jeffrey P.
Abstract: Objectives: To review clinical presentations and management strategies for children with plastic bronchitis. Methods: Retrospective chart review. Results: Seven patients required rigid bronchoscopy to remove bronchial casts over a 17-year study period. Mean age at presentation was 60 months. Mean follow-up was 53 months. Co-morbidities included: congenital heart disease ( n  = 3), chronic pulmonary disorders ( n  = 2) and sickle cell disease ( n  = 1). 4 patients required multiple bronchoscopies for recurrent casts. Adjunctive topical therapies were administered in all 7 patients, without complication. Rigid bronchoscopy for cast removal was performed in 2 patients who were on extra-corporal membrane oxygenation (ECMO), using special precautions to safeguard the ECMO catheters. Conclusions: Bronchial casts in children may present acutely or sub-acutely. Recurrent casts are unusual; however, in combination with severe cardiac disease may lead to mortality. Adjunctive topical therapies are still under investigation. Special safeguards for ECMO catheters are imperative. This case series complements and adds to the International Plastic Bronchitis Registry.